The Brain Rot Phenomenon among Generation Z and Its Implications for Da’wah Communication Practices in the Digital Era - Rafika Rafika; Edhy Rustan; Efendi P; Muhaemin Muhaemin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2026)
The rapid development of digital technology has transformed Generation Z’s interpersonal communication patterns, particularly through the intensive consumption of short-form digital content. This condition has contributed to the emergence of the brain rot phenomenon, referring to cognitive decline caused by excessive exposure to repetitive and superficial digital content. This study aims to analyze the phenomenon of brain rot among Generation Z and its implications for da’wah communication practices in the digital era, focusing on interpersonal communication dynamics in the Luwu Raya region. This study employed a qualitative method using a descriptive phenomenological approach to explore the experiences, meanings, and communication behaviors of Generation Z. Data were collected through in-depth interviews and observations involving Generation Z individuals aged 17–28 years who actively use social media platforms, including TikTok, Instagram, and YouTube. Data analysis was conducted using thematic analysis. The findings reveal three major dimensions affected by the brain rot phenomenon: focal power dynamics, empathy level analysis, and response analysis. The study indicates that brain rot contributes to declining communication focus, reduced empathy, superficial interactions, and instant communication patterns, posing challenges to interpersonal da’wah communication, which requires reflective, empathetic, and meaningful dialogue. Therefore, adaptive and contextual da’wah communication strategies are needed to maintain the effectiveness of religious messages among Generation Z in the digital era.